Methodological And Didactic Conception In Morphophysiology Improves Cognitive Ability - Abreu Ugarte, Jorge Eduardo; Saldaña Bernabeu, A.; Benavides Socarras, O. E.; Cruz García, M. A. (Revista Cubana de Investigaciones Biomédicas, 2019)
Introduction: A current purpose of the medical education is to achieve the prominence of the biomedical subjects in the preparation of the doctors. The suitable motivation is the most adapted way to reach it. In Cuba, the medical teaching has assumed changes with marked incidence in the biomedical subjects. The morphophysiology emerged to integrate with didactic ends the morphological and physiological contents. What created disjunctives about the methods and means for the teaching morphological contents, in front of the tendency to substitute the traditional forms by computer images. It was a problem to resolve by means of the educational search work and methodological scientist. Objective: This work has the aim to value the impact of pedagogical didactic – actions implemented in medicine students of first year to develop cognitive ability in profit of the process of education learning. Methods: The universe was the learning results of the medicine students and the courses among 2008 and 2013 constituted the sample. By random way were taken in each course experimental and control groups. In the first was stimulated the motivation with the method basic on problem, the employment of the optical microscope, histological slides and anatomical pieces. The averages of the experimental groups and controls was compared, in the same manner was compared with total and the accumulated average. Results: The averages of the experimental groups resulted upper to the of the groups control and to the academic average accumulated. Of this way verified the hypothesis posed that the actions implemented in the methodological didactic conception based in the method basic on problem resulted favourable for the development of the cognitive ability of the students. Conclusions: The method basic on problem link with means of traditional education in the morphological sciences, combining them properly with the new means of digitalized images stimulates the motivation, favours the development of cognitive ability and increases the academic results.